Pengaruh Penggunaan Model Pembelajaran Snowball Throwing Terhadap Kemampuan Menulis Teks Deskripsi Siswa Kelas VII SMP N 13 Padang - Chintia Rahmadani; Suci Dwinitia; Ricci Gemarni Tatalia (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2023)
This study aims to describe the skills of writing descriptive text without, with, and how to influence the use of the Snowball Throwing Learning Model on the Writing Ability of Grade VII Students of SMP N 13 Padang. This type of research is quantitative research with experimental methods. The data processed in this study were tests on the results of writing descriptive text skills for class VII students of SMP N 13 Padang. The data collection technique was carried out in 3 meetings, 1 meeting in the control class and 2 meetings in the experimental class. First, students' skills in writing descriptive text before using the Snowball Throwing model for class VII students of SMP N 13 Padang with an average of 73.61 are more than adequate (LdC) because they are at 66% -75% mastery on a scale of 10. Second, writing skills Students' descriptive text before using the Snowball Throwing model for class VII students of SMP N 13 Padang with an average of 84.03 is classified as good (B) because it is at 76% -85% mastery on a scale of 10. Third, students' writing skills of description before using the model Snowball Throwing in learning is better than before using the Snowball Throwing model. Fourth, there is a significant effect, this can be seen from the average value of descriptive text writing skills using the Snowball Throwing Model which is higher than without using the Snowball Throwing Model with a range of (84.03 > 73.60).